Complications after vascularized jejunal mesenteric lymph node transfer: A 3‐year experience. Issue 6 (8th July 2019) - Kraft, Casey T.; Eiferman, Daniel; Jordan, Sumanas; Skoracki, Roman J.
Abstract: Background: Vascularized lymph node transfer (VLNT) is a well‐established method for the surgical management of refractory extremity lymphedema. Generally, donor lymph nodes are harvested from the axilla, groin, or supraclavicular area. However, these sites offer their own disadvantages and introduce risk for inducing lymphedema at the surgical donor site. In our experience, the jejunal mesentery can be an excellent source of lymph nodes without the risk of donor site lymphedema. Long term complications are unknown for this procedure; we report our experience, complication rates, and lessons learned. Methods: A retrospective review was performed for all patients at our institution undergoing surgical treatment of lymphedema using jejunal mesenteric VLNT from February 2015 to February 2018. Demographic data, length of follow up, and surgical complications were reviewed. Results: Twenty‐nine patients have undergone jejunal VLNT at our institution during the three‐year study period, with a total of 30 transfers. Five patients had a concurrent omental lymph node transfer. Average length of follow up was 17.6 months (range 1.0–36.8 months). There was one flap loss in this time frame (3.3%). Four patients developed hernias post‐operatively (13.8%), and three had nonoperative small bowel obstructions (10.3%). One patient had a postoperative wound infection at the abdominal incision (3.4%). Conclusions: Jejunal VLNT can be an effective option for surgical treatment of lymphedema, without the risk of postoperative donor site lymphedema. Patients and surgeons should be aware of the risks of hernia and small bowel obstruction with this method compared to other lymph node sources.